Do Artists Benefit from Resale Royalties? An Economic Analysis of a New EU Directive - Roland Kirstein; Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2000)
According to a new European Union directive, artists, whose works are resold, are entitled to a share of the sales price. The principal aim of this initiative is to let the artists participate in the economic success of their work. Our analysis shows that the new directive is most likely to place the artists in a worse economic position. The analysis of the relation between the artist and his dealer as an incentive compatible contract leads to further objections against the new EU directive. However, the paper also illustrates under which conditions a resale royalty is, at least, an incentive compatible contract.
Keywords: K11; 330; resale rights; droit de suite; Screening Skill; strategic complements; Urheberrecht; Kunst; Verhandlungstheorie; Künstlerische Berufe; EU-Recht; Rechtsökonomik; EU-Staaten; droite de suite